ORTHODONTICS AND DENTAL IMPLANTS: BROADING THE SPECTRUM OF TREATMENT OPTIONS TO IMPROVE DENTAL AND MEDICAL HEALTH IN THE GENERAL POPULATION: A REVIEW - Carvalho, Adilson Alves de; Santana, Washington Macedo de; Neto, João Rosa de Lima; Carvalho, Amilton Alves de; Molina, Omar Franklin (REVISTA CEREUS, 2014)
Introduction: Dentistry in general and orthodontics in particular are always developing new methods to favor both patients in private and public dental practice. Objective: Evaluate the role, advantages, disadvantages, forces and other mechanical variables of dental implants in orthodontics. Methods: A review of the literature using 30 scientific papers both in Portuguese and English. 26 were considered suitable with sufficient data to carry out the review. Results: Most non implant devices used in orthodontics rely on patients´ compliance. Skeletal anchorage using dental implants, mini-plates or mini-screws provide absolute anchorage for tooth movement. Dental implants can be used as an invaluable aid to attain a number of tooth movements including retraction, uprighting, intrusion, mesial and distal movement, closing of edentulous spaces, stabilization, orthopedic traction and repositioning of badly positioned teeth. Dental implants can be placed in many anatomic areas and present advantages including reliable and absolute anchorage. Conclusions: Implantable devices used in orthodontics practice increase orthodontic anchorage, eliminate patient´s compliance need and decrease treatment time. Dental implants can be used to carry out a number of different orthodontic movements which could not be possible without the use of these recently introduced devices. They increase treatment options in private and public health. Keywords: Dental Implants. Tooth Movement. Advantages. Private/Public Health.